Watson Kirkconnell and the "Undoing of Babel": a Little-Known Case in Canadian Translation History - Woodsworth, Judith (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractWatson Kirkconnell (1895-1977) was a scholar, university administrator and prodigious translator of verse from dozens of languages. Yet today he is virtually unknown in the translation community in this country. This article examines the life, work and thought ofKirkconnell, and situates the neglect into which he has fallen in the context of the linguistic landscape of Canada.